Nieciągłość w procesie restrukturyzacji przedsiębiorstwa - Banaszyk, Piotr (Discontinuity in company's restructuring process, 2006)
The contemporary economy is changing conditions of companies' activities. A pressure of competition and a shrinking time of management's reactions are resulting in a management discontinuity. Management by continuous improvement has to be substituted by management by big jump.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 19-24